Characterizing EBV-associated Gastric Carcinoma (EBVaGC): A deep dive into LMP1 expression patterns: EBV-associated gastric carcinoma - Benakli, Yasmina; Khenchouche, Abdelhalim; Rabea, Sameh; Mansour, Ahd A.; Salem-Bekhit, Mounir M.; Taha, Ehab I.; Salem, Mohamed M.; Singh, Soumya; Ould Ouali, Karima; Benguerba, Yacine; Houali, Karim (Cellular and Molecular Biology, 2023)
Gastric cancer (GC) is a serious public health issue due to its frequency and severity. It is, for both sexes, one of the most common causes of cancer-related death and is a major contributor to the global burden of disease. Recent data show that Epstein-Barr virus (EBV) has been detected in different histopathological subtypes of gastric carcinoma and that EBV-associated gastric carcinoma (EBVaGC) represents about 10% of all cases. Moreover, the LMP1 protein characterizing the malignant transformation of cells in several cancer models seems to be very rarely expressed in this type of cancer. This study aimed to characterize EBVaGC in our population by detecting LMP1 in gastric carcinomas in about 30 selected patients. The results showed that in our population, nuclear staining predominates, showing that the antrum remains the most sampled site both for these pathologies and for LMP1 positivity (nuclear staining). In general, the LMP1 marking was negative for 22.58%, positive with a nuclear predominance at 64.52%, nuclear and cytoplasmic at 12.90%, and no positive marking for the cytoplasm. Results were not like the different studies on the expression of this oncogenic protein without EBVsCG, probably finding an explanation in the fact that our country is among the endemic regions for this herpes virus. In conclusion, the rate of LMP1 expression among gastric carcinomas does not seem similar to that observed in other countries. This study characterizing EBVaGC in Tizi-Ouzou, Algeria, reinforces the need for further studies to clarify the role of EBV (LMP1) and to explore its potential value as a predictive biomarker for the development of this type of cancer pathology.